Cryptococcus neoformans urease affects the outcome of intracellular pathogenesis by modulating phagolysosomal pH. - Man Shun Fu; Carolina Coelho; Carlos M De Leon-Rodriguez; Diego C P Rossi; Emma Camacho; Eric H Jung; Madhura Kulkarni; Arturo Casadevall (PLoS Pathogens)
Cryptococcus neoformans is a facultative intracellular pathogen and its interaction with macrophages is a key event determining the outcome of infection. Urease is a major virulence factor in C. neoformans but its role during macrophage interaction has not been characterized. Consequently, we analyzed the effect of urease on fungal-macrophage interaction using wild-type, urease-deficient and urease-complemented strains of C. neoformans. The frequency of non-lytic exocytosis events was reduced in the absence of urease. Urease-positive C. neoformans manifested reduced and delayed intracellular replication with fewer macrophages displaying phagolysosomal membrane permeabilization. The production of urease was associated with increased phagolysosomal pH, which in turn reduced growth of urease-positive C. neoformans inside macrophages. Interestingly, the ure1 mutant strain grew slower in fungal growth medium which was buffered to neutral pH (pH 7.4). Mice inoculated with macrophages carrying urease-deficient C. neoformans had lower fungal burden in the brain than mice infected with macrophages carrying wild-type strain. In contrast, the absence of urease did not affect survival of yeast when interacting with amoebae. Because of the inability of the urease deletion mutant to grow on urea as a sole nitrogen source, we hypothesize urease plays a nutritional role involved in nitrogen acquisition in the environment. Taken together, our data demonstrate that urease affects fitness within the mammalian phagosome, promoting non-lytic exocytosis while delaying intracellular replication and thus reducing phagolysosomal membrane damage, events that could facilitate cryptococcal dissemination when transported inside macrophages. This system provides an example where an enzyme involved in nutrient acquisition modulates virulence during mammalian infection.